ANALISA FAKTOR PENGHAMBAT PENERAPAN BUILDING INFORMATION MODELING DALAM PROYEK KONSTRUKSI - Handika Rizky Hutama; Jane Sekarsari (Jurnal Infrastruktur, 2018)
Utilization of information technology is one of the strategies to improve the performance and competitiveness of enterprises in handling construction projects effectively and efficiently. Building Information Modeling (BIM) is an information system that processes input into information in the form of building modeling as a tool in the decision making process in each stage of the construction project. BIM in construction projects face many obstacles as a result the benefits of its application has not optimal. There is a lack of prior research about analysis of the obstacle factors in the adoption of BIM in construction projects in Indonesia. This study aims to provide information factors and the main obstacle factors the application of BIM in construction projects that benefit the company in improving its application in construction projects. This study was conducted using descriptive statistics, correlation analysis and factor analysis. Data collection techniques by using questionnaires and interviews. The quesioners were distributed to the respondents, the BIM user in construction projects as much as of 40 respondents. The results show that main obstacle factor the application of BIM in construction projects is the lack of participation of management in providing the motivation, training, and supervision as targeted by the company.